The Belt and Road Initiative: Between Pitfalls and Promises a Path Toward a New Humanism (The Macau Ricci Institute Journal, 2019)
When we look at the sheer size and multiple dimensions of the Belt and Road Initiative (BRI) and its related projects we may often wonder how it is possible to come to grips with such a complex beast: Six new land corridors of the “Road” and the Maritime “Belt” throughout the seas, with new spaces around the globe getting more and more connected with each other. Beyond the vast expanses, what could turn out truly as innovative when the BRI was launched in 2013 is the call for reciprocity, peace and cooperation, mutual learning and mutual benefit within it.